Giving Extension Effect On Landslide Disaster Preparedness of Householderâs Knowledge And Attitude - Anggraini, Novita Ana; Sutrisno, Sutrisno; Hasanah, Weni Uswatun (STIKes Surya Mitra Husada, 2018)
Background: The high number of disasters in Indonesia pushed against the need for vigilance on the disaster. preparations to be made by civil society organizations, especially scouts, TAGANA or SARve pretty much done, but preparedness at the family level and the individual is still a lot of efforts increase efforts to improve the preparedness of the family in the face of disaster requires an effort to educate more people, especially in terms of disaster mitigation. Purpose : The aim of this study was to determine the effect of education on disaster preparedness landslides on knowledge and attitude of the head of the family in the hamlet village Jethi Blimbing Mojo Subdistrict Kediri. Methods : This research design is pre-experimental with approach to one group pre-post test, the data obtained using questionnaire. The number of samples taken in this research were 78 respondents, by purposive sampling. Result : Of the total 78 respondents surveyed after being given counseling, 37 respondents (47.4%) had knowledge of preparedness landslides in enough categories and 47 respondents (60.3%) had the attitude of preparedness landslides in the positive category. The analysis in this research for the knowledge using wilcoxon sign rank test statistics obtained p = 0,000<0,05 then H0 is rejected and H1 accepted. Whereas for the attitude using Mc.Nemar statistic test obtained p = 0.001 <0.05 then H0 is rejected and H1 accepted Conclusion : By giving periodic counseling and provision of information continuously, it can affect respondents knowledge about disaster preparedness landslides, because it can affect the stimulus and understand the information provided